Acupuncture Treatment for Patients with Presbyacusis at the Fifa Sehat Clinic in South Jakarta - Pricia Andryani; Ikhwan Abdullah; Amal Prihatono; Puspo Wardoyo (CV. Publikasi Indonesia, 2026)
Presbycusis is a progressive sensorineural hearing loss caused by age-related degenerative processes, significantly affecting an individual's quality of life. This research aimed to describe acupuncture care in a 50-year-old patient with presbycusis to improve hearing function based on the Traditional Chinese Medicine (TCM) approach. The research used a qualitative case study design involving one participant with progressive hearing impairment. Data were collected through TCM examinations, including inspection (Wang), listening and inquiry (Wen), and palpation (Qie), which were analyzed to establish disease and syndrome diagnoses. The results showed that the diagnosis was presbycusis with Kidney Qi deficiency syndrome accompanied by blood (Xue) stagnation. The therapeutic principles included tonifying Qi, strengthening Kidney function, improving blood circulation, and opening the ear orifices. Acupuncture therapy was conducted over 7 days (March 9–15, 2026) with continuous evaluation. The findings indicated gradual improvements in the patient's general condition, including better sleep quality, reduced stress levels, and increased body energy. However, hearing function did not show significant improvement within the short treatment period, although there was a tendency toward stabilization and slight improvement in sound perception. In conclusion, acupuncture therapy demonstrated positive systemic effects and has potential as a complementary treatment to improve the quality of life in patients with presbycusis